Antimicrobial photodynamic activity of toluidine blue encapsulated in mesoporous silica nanoparticles against Pseudomonas aeruginosa and Staphylococcus aureus. Issue 1 (2nd January 2019) - Parasuraman, Paramanantham; Antony, Asha P.; B, Sruthil Lal S.; Sharan, Alok; Siddhardha, Busi; Kasinathan, Kaviyarasu; Bahkali, Needa A.; Dawoud, Turki M. S.; Syed, Asad
Abstract: In the present study, the antimicrobial and antibiofilm efficacy of toluidine blue (TB) encapsulated in mesoporous silica nanoparticles (MSN) was investigated against Pseudomonas aeruginosa and Staphylococcus aureus treated with antimicrobial photodynamic therapy (aPDT) using a red diode laser 670 nm wavelength, 97.65 J cm −2 radiant exposure, 5 min). Physico-chemical techniques (UV-visible (UV-vis) absorption, photoluminescence emission, excitation, and FTIR) and high-resolution transmission electron microscopy (HR-TEM) were employed to characterize the conjugate of TB encapsulated in MSN (TB MSN). TB MSN showed maximum antimicrobial activities corresponding to 5.03 and 5.56 log CFU ml −1 reductions against P. aeruginosa and S. aureus, respectively, whereas samples treated with TB alone showed 2.36 and 2.66 log CFU ml −1 reductions. Anti-biofilm studies confirmed that TB MSN effectively inhibits biofilm formation and production of extracellular polymeric substances by P. aeruginosa and S. aureus .